Research of solar energy at the Faculty of Engineering University of Szeged - Péter Szabó István (Agrár- és vidékfejlesztési szemle, 2011)
At the Faculty of Engineering and it’s legal predecessor – the College Faculty of Food Engineering – we research the utilizing of solar energy since 2004. In our narrower region – the south of the Great Hungarian Plain – the utilizing of solar energy could be advantageous, therewith in our new building we will be able to study the utilization of geothermal heat. With our new equipment we can measure the efficiency and analyze the transient effects of solar collectors.